Functional Roles of Protein Nitration in Acute and Chronic Liver Diseases. (30th April 2014) - Abdelmegeed, Mohamed A.; Song, Byoung-Joon
Abstract : Nitric oxide, when combined with superoxide, produces peroxynitrite, which is known to be an important mediator for a number of diseases including various liver diseases. Peroxynitrite can modify tyrosine residue(s) of many proteins resulting in protein nitration, which may alter structure and function of each target protein. Various proteomics and immunological methods including mass spectrometry combined with both high pressure liquid chromatography and 2D PAGE have been employed to identify and characterize nitrated proteins from pathological tissue samples to determine their roles. However, these methods contain a few technical problems such as low efficiencies with the detection of a limited number of nitrated proteins and labor intensiveness. Therefore, a systematic approach to efficiently identify nitrated proteins and characterize their functional roles is likely to shed new insights into understanding of the mechanisms of hepatic disease pathophysiology and subsequent development of new therapeutics. The aims of this review are to briefly describe the mechanisms of hepatic diseases. In addition, we specifically describe a systematic approach to efficiently identify nitrated proteins to study their causal roles or functional consequences in promoting acute and chronic liver diseases including alcoholic and nonalcoholic fatty liver diseases. We finally discuss translational research applications by analyzing nitrated proteins in evaluating the efficacies of potentially beneficial agents to prevent or treat various diseases in the liver and other tissues.